Effect of carbonated drink on excisional palatal wound healing: A study on Wistar rats - Suragimath Girish; Krishnaprasad K; Moogla Srinivas; Sridhara Sudheendra; Raju Shashidara (Wolters Kluwer Medknow Publications, 2010)
Background: Millions of people worldwide consume carbonated drinks every day. The effects of these drinks on hard tissues in the mouth have been proved beyond doubt. Only a little has been done so far to assess the effects of carbonated drinks on oral soft tissues. This study was an attempt to assess the effect of carbonated drinks on oral wound healing. Materials and Methods: Twenty female Wistar rats were considered for the study. A circular wound was created on the palate and the animals were divided into two groups (experimental and control group). The experimental group animals were fed with a commercially available carbonated drink instead of water, and two animals from each group were euthanized at 3, 7, 14 and 21 days. Wound site was assessed morphometrically and histologically. Results: There was a marked difference in the healing pattern between the experimental group and control group animals. Control group animals showed a normal healing pattern with formation of a fibrous connective tissue at the end of 21 days. In the experimental group, healing was delayed and disrupted. The wound site showed a definite palatal perforation in experimental group animals after 14 days, but osteoclasts were not noticed in the histological sections. Conclusion: Consumption of carbonated drinks can disrupt oral wound healing. Results suggest that the bone changes seen in experimental group samples are not mediated by osteoclasts, and acidity of the carbonated drinks could be one of the reasons for these changes.